2001
DOI: 10.1093/hmg/10.21.2415
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations in COL8A2, the gene encoding the alpha2 chain of type VIII collagen, cause two forms of corneal endothelial dystrophy

Abstract: Corneal clarity is maintained by its endothelium, which functions abnormally in the endothelial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
308
2
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(320 citation statements)
references
References 33 publications
1
308
2
9
Order By: Relevance
“…Moroi et al [2003] also indicated that PPCD in family UM:139 is unlikely to be the result of a mutation at the autosomal dominant congenital hereditary endothelial dystrophy locus (CHED1 [MIM121700]) located within and potentially allelic to the chromosome 20q PPCD locus [Toma et al, 1995], the autosomal recessive CHED2 locus (MIM217700) on chromosome 20p [Chan et al, 1982;Hand et al, 1999]. This paper also found that PPCD in this family is unlikely to be the result of mutations in the COL8A2 gene (MIM120252) on chromosome 1p [Biswas et al, 2001], which causes Fuchs endothelial corneal dystrophy (FECD) and has been given the alias PPCD2 by the Human Genome Nomenclature Committee because of the observation of a COL8A2 FECD mutation in two members of one PPCD family [Biswas et al, 2001]. In this study we provide significant evidence of a new PPCD locus, PPCD3, and discuss phenotypic variability within a single large family with PPCD.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Moroi et al [2003] also indicated that PPCD in family UM:139 is unlikely to be the result of a mutation at the autosomal dominant congenital hereditary endothelial dystrophy locus (CHED1 [MIM121700]) located within and potentially allelic to the chromosome 20q PPCD locus [Toma et al, 1995], the autosomal recessive CHED2 locus (MIM217700) on chromosome 20p [Chan et al, 1982;Hand et al, 1999]. This paper also found that PPCD in this family is unlikely to be the result of mutations in the COL8A2 gene (MIM120252) on chromosome 1p [Biswas et al, 2001], which causes Fuchs endothelial corneal dystrophy (FECD) and has been given the alias PPCD2 by the Human Genome Nomenclature Committee because of the observation of a COL8A2 FECD mutation in two members of one PPCD family [Biswas et al, 2001]. In this study we provide significant evidence of a new PPCD locus, PPCD3, and discuss phenotypic variability within a single large family with PPCD.…”
Section: Introductionmentioning
confidence: 78%
“…Since the homeodomain transcription factor VSX1 has been implicated in PPCD [Heon et al, 2002], it is of interest to note that the PPCD3 critical interval contains the transcription factor, TCF8 (MIM189909), which has both homeodomain and zinc finger motifs [Williams et al, 1992;Funahashi et al, 1993;Franklin et al, 1994;Kent et al, 2002]. Although several collagen genes have been implicated in PPCD [Biswas et al, 2001] and in Alport syndrome, which can include PPCD [Colville and Savige, 1997;Kashtan, 1999], none of the known collagen genes are located in the interval between D10S213 and D10S578. Prioritization of candidate genes within this interval will call for additional bioinformatic analysis and evaluation of gene expression in relevant ocular tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease is characterized by accumulation of extracellular collagenous deposits called "guttae" posterior to Descemet's membrane, the specialized extracellular matrix that backs the corneal endothelium [111]. Earlyonset FECD has been linked genetically to a mutation in the COL8A2 (2 chain of collagen VIII) gene encoding a component of Descemet's membrane [112]. Polymorphisms in the CLU gene have been associated with late-onset FECD [113,114].…”
Section: Corneal Dystrophies -This Is a Group Of Inherited Disorders mentioning
confidence: 99%
“…1 Endothelial cells from affected corneas demonstrate characteristics of epithelial cells including the ability to proliferate, leading to focal formation of multilayered areas, and multilamination of Descemet membrane. [2][3][4] PPCD is genetically heterogeneous with three identified loci; PPCD1 (OMIM #122000) on chromosome 20p with a currently undefined causative gene, [5][6][7] PPCD2 (OMIM #609140) associated with mutations in COL8A2, 8 and PPCD3 (OMIM #609141) caused by mutations in ZEB1. 9 To date, over 30 heterozygous nonsense and frameshifting mutations in ZEB1 have been identified.…”
Section: Introductionmentioning
confidence: 99%